The effects of demography, expectations and student attitudes on Australian secondary school teachers' homework practices - Bowd, Justin; Bowles, Terry; McKenzie, Vicki (The Australian journal of education, 2021)
Homework has been associated with a range of academic and cognitive benefits for secondary students. Research has also revealed that students' homework behaviours can vary with demographic traits. An important factor that may account for some of this variation is the role played by teachers and schools in homework allocation. It is hypothesised that some of the demographic variables that have been found to predict individual students' homework practices are also related to teachers' practices in terms of the frequency and volume of homework allocated at the classroom level. To test this hypothesis, Australian data from the 2015 Trends in International Mathematics and Science Study are analysed in the current study. Results show that the frequency of mathematics homework allocated by teachers is related to some variables that have commonly predicted the differences in student achievement such as socioeconomic status, valuing of and confidence in mathematics, teaching experience and school location. The implications of these findings for schools and education systems are explored as suggestions for ensuring that homework policies and practices do not exacerbate demographic differences in school outcomes. [Author abstract]